Molecular surveillance of non-polio enterovirus infections in patients with acute gastroenteritis in Western India: 2004-2009 - Patil, Pooja R.; Chitambar, Shobha D.; Gopalkrishna, V. (Journal of medical virology, 2015)
Acute gastroenteritis is a major cause of childhood morbidity and mortality worldwide. Rotavirus (RV) and Norovirus (NoV) are the leading cause of the disease. Despite the use of improved diagnostic methods a significant proportion of gastroenteritis cases remained undiagnosed. Though nonpolio enteroviruses (NPEVs) have been reported frequently in children with acute gastroenteritis, their etiologic role has not been established. To investigate the epidemiology of NPEVs in gastroenteritis cases which remained negative for leading causative agents, 955 RV and NoV negative stool specimens from children hospitalized for acute gastroenteritis were included in the study. A case control study was conducted which includes stool specimens from 450 children with gastroenteritis and 162 asymptomatic control subjects to determine the association of NPEVs with the disease. NPEV detection and typing was carried out by RT‐PCR and sequencing. Presence of RV, NoV, Adenovirus, and Astrovirus was confirmed by ELISA or PCR/RT‐PCR. Overall 14% NPEV prevalence was noted. The percentage of children with NPEV infection differed significantly between gastroenteritis and non‐gastroenteritis patients (13.7% vs. 4.9%). NPEV was more prevalent among patients with gastroenteritis of undetectable etiology as compared to those detected positive for other viruses (17.9% vs. 7%) (P < 0.01). Genotyping of NPEV identified predominance of EV‐B species (56.5%) followed by EV‐C (16.7%), EV‐A (13.8%) species and mixed NPEV infections (13%). These data support the association of NPEVs with acute gastroenteritis and highlights the clinical and epidemiological features of NPEV infections in patients with acute gastroenteritis from western India. J. Med. Virol. 87: 154–161, 2015. © 2014 Wiley Periodicals, Inc.